MO1024CLOSTRIDIUM SEPTICUM INFECTION COMPLICATING HEMOLYTIC UREMIC SYNDROME: A CASE REPORT AND LITERATURE REVIEW. (29th May 2021) - Cirillo, Luigi; Becherucci, Francesca; Guzzi, Francesco; Errichiello, Carmela; Buti, Elisa; Roperto, Rosa Maria; Materassi, Marco; Romagnani, Paola
Abstract: Background and Aims: C.septicum is an anaerobic bacterium that resides in the gastrointestinal tract of herbivores. Its presence in human fecal flora is still debated, being found in only 2.8% of healthy adults. Transmitted by oral-fecal route, it reaches the systemic circulation, causing bacteremia, myonecrosis, bowel necrosis, intracranial abscesses/encephalitis. Shiga-toxin producing E. Coli related hemolytic uremic syndrome (STEC-HUS) is a thrombotic microangiopathy characterized by hemolytic anemia, thrombocytopenia and kidney damage, related to STEC infection. Severe presentation includes gastrointestinal and neurologic involvement. Microangiopathic lesions in the colonic mucosa can facilitate the colonization of systemic circulation by C.septicum, spreading the superinfection. Since the first report in 1988, very few cases of STEC-HUS complicated by C.septicum superinfection have been described in literature and thus the factors predicting clinical outcome are not clear. Method: We describe the case of a 5-years-old girl admitted for anemia, AKI, thrombocytopenia and diarrhea. Previous history was unremarkable. STEC-HUS diagnosis was made. Despite prompt conservative treatment, 12h later her clinical condition worsened, showing ESKD needing dialysis, abdominal pain, progressive hyporesponsiveness. The brain CT scan showed pneumocephalus and encephalitis; blood cultures were drawn and broad-spectrum antibiotic therapy was set (Tab.1 ). Cardiovascular instability prevented surgical treatment of pneumocephalus to be done. The patient died shortly after because of septic shock. Post-mortem stool and blood cultures confirmed STEC infection complicated by C.Septicum. Previous literature on this specific clinical picture has been reviewed and summarized. Results: Eleven additional cases (7 males) have been previously described. Mean age of presentation was 2.9 years. A; abdominal symptoms (commonly distention and pain) were reported in all cases, while ESRD was present in 10 cases. Six patients presented fever. Central nervous system presentation as pneumocephalus was associated with poor prognosis, while surgical treatment availability of brain lesions to survival. In one case the infection caused myonecrosis (Tab. 1 ). The mortality rate was about 60%. In 7 cases, clinical conditions worsened in less than 24h and this was in all cases related to poor outcome. Conclusion: C.septicum superinfection complicating STEC-HUS is a rare but fearsome complication to be aware of. Rapid diagnosis and surgical treatment are essential for the successful management of this particular condition.